Conditioned Taste Aversion as a Tool for Mitigating Human-Wildlife Conflicts - Snijders, Lysanne; Thierij, Nina M.; Appleby, Rob; St. Clair, Colleen C.; Tobajas, Jorge (Frontiers in Conservation Science, 2021)
Modern wildlife management has dual mandates to reduce human-wildlife conflict (HWC) for burgeoning populations of people while supporting conservation of biodiversity and the ecosystem functions it affords. These opposing goals can sometimes be achieved with non-lethal intervention tools that promote coexistence between people and wildlife. One such tool is conditioned taste aversion (CTA), the application of an evolutionary relevant learning paradigm in which an animal associates a transitory illness to the taste, odor or other characteristic of a particular food item, resulting in a long-term change in its perception of palatability. Despite extensive support for the power of CTA in laboratory studies, field studies have exhibited mixed results, which erodes manager confidence in using this tool. Here we review the literature on CTA in the context of wildlife conservation and management and discuss how success could be increased with more use of learning theory related to CTA, particularly selective association, stimulus salience, stimulus generalization, and extinction of behavior. We apply learning theory to the chronological stages of CTA application in the field and illustrate them by synthesizing and reviewing past applications of CTA in HWC situations. Specifically, we discuss (1) when CTA is suitable, (2) how aversion can be most effectively (and safely) established, (3) how generalization of aversion from treated to untreated food can be stimulated and (4) how extinction of aversion can be avoided. For each question, we offer specific implementation suggestions and methods for achieving them, which we summarize in a decision-support table that might be used by managers to guide their use of CTA across a range of contexts. Additionally, we highlight promising ideas that may further improve the effectiveness of CTA field applications in the future. With this review, we aspire to demonstrate the diverse past applications of CTA as a non-lethal tool in wildlife management and conservation and facilitate greater application and efficacy in the future.